HUBUNGAN ANTARA KOMPETENSI GURU DENGAN MOTIVASI BELAJAR PADA SISWA BOARDING SCHOOL SMP PLUS AL-AQSHA - Siti Homisati Solihah; Ulfiah Ulfiah; Ening Ningsih (Psympathic : Jurnal Ilmiah Psikologi, 2012)
Teacher competences is a capability in doing teaching learning process in the class. That competences expected making the students respect to the teacher, enjoy the learning process and increase their motivation. According to Barloe (1985) teacher competences  are teacher capability in doing their work and responsilibity. Meanwhile, learning motivation is students psychological effort that encourage learning activity and give direction on learning to get a certain goal (Winkel, 2009). This research used correlational design and Rank Spearman formula. Subject are 130 grade IX Junior High School students. Probability value is 0,001 which is less than α= 0,05. It means that Ho is rejected and it is concluded that there is positive correlation between teacher competences and learning motivation.